Peatlands Are More Beneficial if Conserved and Restored than Drained for Monoculture Crops - Tarigan, Suria; Zamani, Neviaty P.; Buchori, Damayanti; Kinseng, Rilus; Suharnoto, Yuli; Siregar, Iskandar Z. (Frontiers in Environmental Science, 2021)
Peatlands are especially important but fragile tropical landscape. The importance of peatlands is due to its ability to: a) sequester huge amount of terrestrial carbon, b) store freshwater, and c) regulate floods during rainy season. Nowadays extensive peatland degradation occurs due to its utilization for agriculture activities causing serious environmental consequences such as carbon emission, loss of biodiversity, flooding risk, and peat fire. Meanwhile, local planners and decision makers tend to oversee long term strategic function of peatland for carbon storage and hydrological regulation preferring peatland utilization for short term economic benefit. The objective of our study is to quantify total ecosystem service (except biodiversity) of a tropical peatland landscape in different peat utilization scenarios to help build awareness of local planner and decision maker on the strategic trade-off of peatland utilization. Studies of total ecosystem services involving hydrological regulation is still rare in a tropical peatland landscape. Based on the net present value calculation, the provisioning, the carbon regulation, and the hydrological regulation in our study area account for 19%, 70%, 11% of the total ecosystem services, respectively. Based on the uncertainty analysis, that at any combination of social cost of carbon (within range of USD 52.7 – USD 107.4) and discount rate (within range 0f 5-10%), enrichment of peatlands with paludiculture crop (e.g. jelutong) shows superior ecosystem services compared to other utilization scenarios. In contrast, planting peatland with monoculture crop associated with peatland drainage show a sharp decrease in the total ecosystem services. The fluvial carbon export in our study, which is often neglected in the peatland carbon budget, increases the estimate of total carbon budget by 8%. The restoration on undrained peatland with paludiculture crop such as jelutong contribute positively to carbon sequestration and potentially reduce carbon emission of 11%. These quantitative findings can help local planners and decision makers to realize the trade-off of a long term benefit of peatland restoration over short term economic benefit of peatland utilization for monoculture crops.